2011
DOI: 10.1111/j.2041-1014.2011.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antigen‐presenting cells induced by intragastric immunization with recombinant chimeric immunogens constructed from Streptococcus mutans AgI/II and type I or type II heat‐labile enterotoxins

Abstract: SummaryIntragastric (i.g.) immunization with recombinant chimeric proteins constructed from the salivabinding region (SBR) of Streptococcus mutans surface antigen AgI/II and the A2/B subunits of enterobacterial heat-labile enterotoxins has been successfully used to induce salivary and circulating antibodies against S. mutans that have protective potential against dental caries. To investigate the mode of action of these vaccine constructs, mice were immunized i.g. with chimeric proteins constructed from SBR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
(92 reference statements)
1
11
0
1
Order By: Relevance
“…Overall, this indicates that signals from several APCs are required to lead to the formation of vWFA2-reactive CD4 T cells. Previous studies showed that different APCs were required in the Agpresenting process (50)(51)(52). Particularly in the collagen-induced arthritis model in rats, similar results like in our model were observed (50).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, this indicates that signals from several APCs are required to lead to the formation of vWFA2-reactive CD4 T cells. Previous studies showed that different APCs were required in the Agpresenting process (50)(51)(52). Particularly in the collagen-induced arthritis model in rats, similar results like in our model were observed (50).…”
Section: Discussionsupporting
confidence: 89%
“…Our results suggest that the adjuvant effect of heat-labile toxins favors the generation of antibodies against conformational determinants relevant for the function of the P1 adhesin. Previous studies employing the saliva-binding region (SBR) of P1 have also reported positive results when the immunogen was administered in combination with different LT derivatives, either as an isolated polypeptide or as a chimeric protein genetically fused to the B subunit of cholera toxin (52,53).…”
Section: Figmentioning
confidence: 99%
“…As a mediator of sucroseindependent attachment, P1 is an important target of such antibodies (21,22,27,(52)(53)(54)(55). To infer the potential protective effects conferred by immunization with P1 39 -512 , we determined if serum samples collected from vaccinated mice would reduce the initial adhesion of S. mutans to the dental surface of nonimmunized mice.…”
Section: Figmentioning
confidence: 99%
“…This finding raises the question of what cells are involved in the uptake and processing of SBR-CTA2/B at mucosal surfaces, leading to the induction of antibody responses. In a previous study (16), we investigated the antigen-presenting cells (APC) induced by i.g. immunization with recombinant chimeric immunogens prepared from SBR and the A2/B subunits of CT or the type II heat-labile enterotoxins, LT-IIa or LT-IIb.…”
mentioning
confidence: 99%
“…We found that the chimeric immunogens induced the upregulation of costimulatory molecules on APC recovered from Peyer's patches (PP) and mesenteric lymph nodes (MLN). CD11c ϩ dendritic cells (DC) were identified as major APC in the PP and MLN (16). However, that study did not have the resolution to determine where chimeric immunogens were taken up in the intestinal tract, what cells were involved in the uptake, and how immune responses were initiated.…”
mentioning
confidence: 99%